Contagious Magic: Metonymic Shifts in Spanish-English Poetry Translation - Washbourne, Kelly (Transletters. International Journal of Translation and Interpreting, 2022)
Metonymy has slowly begun to get its due in tropological research involving translation, although it lags well behind metaphor. This study starts from the difficult mapping of metonymy across several subtypes, its manifestations as conceptual metonymy, and its imbrications with cognitive poetics and metaphor; leaving aside translating metonymic instances themselves, the work examines the 'metonymic reading' performed in published Spanish-English poetry translations. The overarching goal is to explore how the metonymic characterization of translation processes can help nuance our understanding of related techniques such as modulation, and to recognize, translate, and assess semantic relations more knowledgeably through metonymic thinking.